2021
DOI: 10.3390/medicina57121353
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of COVID-19 on Healthcare Workers and Non-Healthcare Workers in Mexico: 14 Months into the Pandemic

Abstract: Background and Objectives: Healthcare workers (HCWs) play important roles in mitigating the COVID-19 pandemic and are more likely to become infected with COVID-19. Mexico, among other countries, had a high incidence and prevalence of cases and deaths from this disease. Material and Methods: This retrospective study evaluated the clinical characteristics as well as the geographical distribution of cases, deaths, and active cases of COVID-19 in HCWs and non-HCWs using official information from the Ministry of He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
(13 reference statements)
1
7
0
Order By: Relevance
“…This systematic review included 73 935 participants (54 585 dentists and 19 350 dental assistants/technicians) from 14 countries. Four studies were performed in Asia, 29–32 eight in Europe, 32–39 three in South America 40–42 and two in North America 43–45 . The mean age of participants ranged from 38 to 46 years, and the number of females ranged from 58% to 89%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This systematic review included 73 935 participants (54 585 dentists and 19 350 dental assistants/technicians) from 14 countries. Four studies were performed in Asia, 29–32 eight in Europe, 32–39 three in South America 40–42 and two in North America 43–45 . The mean age of participants ranged from 38 to 46 years, and the number of females ranged from 58% to 89%.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were performed in Asia, [29][30][31][32] eight in Europe, [32][33][34][35][36][37][38][39] three in South America [40][41][42] and two in North America. [43][44][45] The mean age of participants ranged from 38 to 46 years, and the number of females ranged from 58% to 89%. Systemic conditions or comorbidities varied across studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…During the COVID-19 pandemic, work-related stress ramped up because of mandatory changes [ 48 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ]. Several surveys [ 61 , 64 , 65 , 67 , 68 , 70 , 71 , 95 ] conducted during the COVID-19 outbreak in different countries have revealed a sensible impact of it on radiologists’ life in terms of anxiety, fear of spreading the infection, difficulty sourcing PPE, shifts in workload due to an increase in emergency procedures, and feeling that the crisis had affected their family relationships and damaged their own and their colleagues’ professional activity.…”
Section: Discussionmentioning
confidence: 99%
“… 23 A survey form Mexico found the prevalence of COVID-19 among dentist, 14 months into the pandemic, to be 1.6%. 24 A study on COVID-19 seroprevalence in UK oral healthcare workers concluded that enhanced personal protection equipment and infection control practices reduced the risk of occupational exposure to SARS-CoV-2 to background population levels. 25 Based this data it is not possible to know whether dentist were infected with the virus during patient care.…”
Section: Discussionmentioning
confidence: 99%